Berteologi Multidisipliner dan Interkultural di Zaman Migrasi - Martinus Dam Febrianto (Jurnal Teologi (Journal of Theology), 2020)
InLaudato Si(2015), Pope Francis offers a contextual theological reflection on humanitys relationship with the planet. Widely considered as a theological discourse par excellence, the papal encyclical combines theological reflections with studies from various scientific disciplines. The result is a theology that is both contextual and relevant to the challenges of the present world. Against this backdrop, this article argues that the development of a theology of migration in recent decades presents an attempt to conduct theological inquiries in a manner consonant to Pope Francis theological method. This is due to the method used in migration theology. It begins by reflecting upon concrete phenomena and encounters (interculturality). Subsequently, it considers multidisciplinary scientific analyses. Finally, it offers practical consequences for both moral and pastoral decisions. This article aims to describe the approaches taken by contemporary theologians in their attempts to develop a multidisciplinary and intercultural migration theology. Moreover,it seeks to show that migration theology can be an importantlocusfor a public theology, as it is able to enter into the realm of discourse and dialogue with the wider public for the sake of the common good.